Comparative Study on Students' Engagement and Academic Outcomes in Live Online Learning at University - Aleksandra Kobicheva (MDPI AG, 2022)
Many studies have assessed students' engagement with learning and academic outcomes and studied the influence of the engagement level on academic outcomes. Nevertheless, there are few studies that demonstrate the results of live online learning and reveal whether gender or/and education level mediates the relationships between students' engagement and academic outcomes. A total of 301 under- and postgraduate students from the Humanity Institute of Peter the Great Polytechnic University voluntarily participated in this study. We conducted online surveys to reveal the level of students' engagement and academic outcomes in the process of live online learning and analyzed the associations between these variables. Results displayed higher levels of engagement and academic outcomes for females, and the difference between the results was significant, particularly for behavioral and emotional engagement (p < 0.001). Significant differences of the measurement factors including behavioral engagement (p < 0.01), cognitive engagement (p < 0.01), and academic outcomes (p < 0.05) were revealed between undergraduate (UG) and postgraduate (PG) students. The findings obtained by using the linear regression analysis technique indicated that engagement scores significantly predict the students' academic outcomes for both females and males, while UG and PG students demonstrated different results. It was detected that cognitive engagement has a greater effect on academic outcomes for PG students, while behavioral engagement has a greater effect on academic outcomes for UG students.